(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2026)
Contemporary Islamic Studies faces a methodhological crisis rooted in the epistemological dichotomy between the religious sciences and the general sciences. This crisis has resulted in a troubled relationship, hindering the relevance of Islamic scholarship in responding to contemporary challenges. This article aims to explore methodological renewal through pluridisciplinary, multidisciplinary, and transdisciplinary approaches as a coherent epistemological solution. This study employs a library research method with a descriptive-analytical approach. The analysis focuses on the key works of M. Amin Abdullah, Mulyadhi Kartanegara, Seyyed Hossein Nasr, Ziauddin Sardar, Ian G. Barbour, Jasser Auda, and Faqihuddin Abdul Kodir. The findings indicate that effective renewal is not merely an addition of disciplines but a complete, four-layered epistemological reconstruction. First, the adoption of the "Three Keys" (Semipermeable, Intersubjective Testability, Creative Imagination) as a philosophical prerequisite for dialogue. Second, a structural paradigm shift from the hierarchical "Tree of Knowledge" model to the interconnective "Spider-Web of Knowledge". Third, a methodological evolution in fiqh through the Maqashid al-Syari’ah paradigm, shifting from "protection" (hifz) to "development" (tanmiyah). Fourth, methodological innovation in tafsir through contextual-progressive approaches such as semantics and qira’ah mubadalah. This renewal offers a vital integrative-interconnective framework for the relevance of Islamic Higher Education Institutions (IHEI) in the contemporary era.